Factors associated with the effectiveness of interventions to prevent obesity in children: a synthesis of evidence from 204 randomised trials - Deborah M Caldwell; Julian P T Higgins; Theresa H M Moore; Carolyn D Summerbell; Jelena Savović; Francesca Spiga; Jennifer C Palmer; Eve Tomlinson; Annabel L Davies (BMJ Public Health)
Introduction We aim to identify effective characteristics of behavioural change (physical activity and diet) interventions that prevent obesity in children aged 5 to 18 years.Methods We re-analysed data from two Cochrane systematic reviews published in 2024 using a Bayesian multi-level meta-regression analysis with intervention and trial characteristics coded according to an analytic framework co-developed with stakeholders.Results We included 204 trials (255 intervention arms) reporting data on body mass index (BMI), either unstandardised or measured as a z-score (zBMI) or percentile. Interventions were effective on average (MD in zBMI −0.037, 95% credible interval −0.053 to −0.022). The greatest effects were associated with medium-term follow-up (nine to <15 months) and older children (12 to 18 years). We found evidence of small beneficial effects for interventions targeting physical activity alone compared with diet alone (difference in MDs −0.227,–0.362 to −0.090) and small unfavourable effects for interventions that involved a change to the structural environment (typically the school food environment) (difference in MDs 0.05, 0.017 to 0.085). Accounting for interactions between covariates, the most effective combination of intervention characteristics was to intervene in the school setting, with an individualised element to delivery, targeting physical activity, using multiple strategies of short duration and high intensity and involving modification of behaviour through participation in activities.Conclusions The most effective characteristic to include in a behavioural change intervention to prevent obesity in children aged 5–18 years was targeting of physical activity. This should not be interpreted as evidence that attempts to modify diet are not beneficial. Being physically active and consuming a healthy diet during childhood offer many important benefits beyond contributing to healthy weight and growth. Our findings suggest that interventions to prevent obesity in children should consider increasing their focus on the promotion of physical activity and consider other effective characteristics we identify here.